Prototyping of DSSDs for Particle Tracking and Spectroscopy within the EXL Project at Fair - Chung, Le Xuan; Egelhof, P.; Ilieva, S.; Streicher, B.; Borger, R.; Rigollet, C.; Kalantar-Nayestanaki, N.; Najafi, A.; Davinson, T.; Woods, P. J.; et al. (Communications in Physics, 2012)
Prototype double-sided silicon strip detectors (DSSD\(s\)) of 300 \(μ \)m thickness produced at PTI St. Petersburg (Russia) were tested for the use as position sensitive, \(Δ E\) and E detectors for tracking and particle identification in the EXL (EXotic nuclei studied in Light-ion induced reactions at the NESR storage ring) setup at the FAIR (Facility for Antiproton and Ion Research) project at GSI. We describe the characteristics of detectors with \(16 × 16, 64× 64\) and \(64× 16\) strips, respectively. The response of these detectors for \(^241\)Am \(α\) particles injected either from the p or n side was examined. The test measurements were performed partially at GSI and the University of Edinburgh. A first in-beam test with a proton beam of 50 MeV with the latter two DSSDs and two 6.5 mm thick Si(Li) detectors was also done at KVI Groningen, the Netherlands. The results reveal good spectroscopic properties of these detectors.